Efecto de la fertilización nitrogenada en la composición bromatología y degradación in vitro de la veranera (Cratylia argéntea) durante la época seca - Yépez Guillen, Niepcer Arnold (2022)
The research was carried out at the “La María” Campus of the State Technical University of Quevedo. The objective of the research was to evaluate the effect of nitrogen fertilization on the bromatology composition, degradability and in vitro degradation of veranera during the dry season. Four treatments were evaluated (T1:0g plant Nitrogen/cut-1, T2:16 g plant Nitrogen/cut-1, T3: 37 kg plant Nitrogen/cut-1, T4:59 kg plant Nitrogen/cut-1), and 4 repetitions, the variables were analyzed using PROC GLM from SAS (2011). For the comparison of means, the Tukey test was used except for the in vitro ruminal degradation kinetics of DM, OM, NDF and FDA, which was analyzed with the Graphpad Prism 6 program. In the variables evaluated we have the bromatological composition (DM ,MO,PC,FDN,FDA), in vitro digestibility (MS,MO,FDN,FDA) and in vitro ruminal degradability (MS,MO,FDN,FDA). Regarding the bromatological composition, no significant difference was observed, however in crude protein there was an increase in T3 and T2 (22.96 and 22.51% respectively). Within the parameters of in vitro digestibility, no significant difference was recorded either, except for the FDN, which did record differences in T2 (31.39%). On the other hand, within the in vitro degradation, no significant differences were recorded within the treatments. It is concluded that nitrogen fertilization influences the increase in crude protein and is more digestible for the NDF component. It is recommended to carry out the same investigation in the rainy season and on longer mowing days.